SISTEM PAKAR DIAGNOSA KARAKTERISTIK PENYALAHGUNAAN NARKOBA MENGGUNAKAN METODE FORWARD CHAINING - Rinny Asasunnaja; Khairan AR AR; Rahmat Musfikar (PTE FTK UIN Ar-Raniry, 2020)
This research is motivated by the number of drug cases in Indonesia, so that the number of users in 2017 reached 3,376,115 users in the 10-59 years age group. This is a very serious problem, and to prevent this from becoming a more serious problem it is recommended that parents, neighbors and relatives need to take the first step by identifying drug users through their characteristics. This study aims to build an expert system to diagnose the characteristics of drug users using the forward chaining method. The research method used is Research & Development and for system testing using black box testing techniques. Then the user acceptance of the system is tested and the results obtained are positive responses with a percentage rate of 86%, which means that the expert system that is designed is very feasible so that it can provide convenience.